2006
DOI: 10.1111/j.1742-7843.2006.pto_471.x
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Predicting Drug Toxicity in silico

Abstract: Poor pharmacokinetics, side effects and compound toxicity are frequent causes of late-stage failures in drug development. A safe in silico identification of adverse effects triggered by drugs and chemicals would be highly desirable as it not only bears economical potential but also spawns a variety of ecological benefits: sustainable resource management, reduction of animal models and possibly less risky clinical trials. In computer-aided drug discovery, both existing and hypothetical compounds may be studied;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 78 publications
0
55
0
3
Order By: Relevance
“…Vedani et al, 2005b). m...... (Vedani et al, 2006); the Raptor model depicts the thyroid [3 receptor (Vedani at al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vedani et al, 2005b). m...... (Vedani et al, 2006); the Raptor model depicts the thyroid [3 receptor (Vedani at al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This protocol was applied to the estrogen receptor alß. (Vedani et al, 2005b;Peristera and Vedani, in preparation), androgen receptor , the peroxisome proliferator-activated receptor y (Vedani et al , 2007), the glucocorticoid receptor (Spreafico et al, in preparation) and the enzyme cytochrome P450 3A4 (Lill et al, 2006). For the aryl hydrocarbon receptor, for which no experimental structure is available, the alignment was performed based on the molecular skeletons (Vedani et al, 1999a(Vedani et al, , 1999b(Vedani et al, , 2003(Vedani et al, , 2005aVedani and Dobler, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As introduced above, many purchasable compounds or virtual compounds may not have satisfactory ADME/Tox properties to be considered as promising drug candidates. It is then possible to remove from the libraries some of these molecules by computing properties such as: absorption prediction via computation of logP, logD, molecular weight, polar surface area (e.g., if greater than 140 Å 2 , poor intestinal absorption), number of H-bond donors-acceptors, number of rotatable bonds (see Lipinski rule of 5 reviewed in [191]), frequent hitters, reactive chemical groups, etc) using in silico methods ( [191][192][193][194][195][196][197][198][199]) (Table III). It is commonly accepted that absorption, distribution and excretion are dependent on similar descriptors while metabolism and toxicity are of a quite different nature and depend of numerous factors.…”
Section: Virtual Ligand Screening: Strengths and Limitationsmentioning
confidence: 99%
“…However, in the recent years, more and more evidence has shown that many drugs exert their activities by modulating multitargets [2][3][4]. Besides, some drugs interact with antitargets and induce strong side effects [5,6]. Therefore, it is inappropriate to stick to the paradigm that drug interacts with only one target.…”
Section: Introductionmentioning
confidence: 99%